Bearing Capacity of Ring Footing Erected on Wet Gypseous Soil - Khudur Ali Eid; Asst. Prof. Dr. Adnan Jayed Zedan; Asst. Prof. Dr. Lamyaa Najah Snodi (Zien Journals, 2023)
In this research, (24) experiments were conducted for a ring basis on gypsum soil submerged in water for 24 hours before the examination, where the ratio of inner diameter / outer diameter (Di / Do) is (0, 0.2,0.3, and 0.4) and gypseous soil is of two types: the first soils with a low gypsum content (8.15%) obtained from the Baiji region and the second soils with a high gypsum content (63.42%) from the University of Tikrit. The experiments are conducted using a steel box with dimensions of (900 * 900) mm and a height of (700) mm. The experiments were divided into (12) examinations of flooded soils with low gypsum content using field density (14.87 kN/m3 ), and (12) examinations of dry soil with high gypsum content using field density (13.76 kN/m3 ). Experiments were conducted on a different depth/diameter ratio of the foundation (Df/D) (0, 0.5, and 1). The results showed that the ring footing is better than the circular footing. The best ratio was (Di / Do = 0.4) for all ratios (Df/D). Bearing capacity increases with increasing ratio (Df / D), but this increase is small and gives high subsidence and danger in the initial loading stages that cause the collapse of buildings built on gypsum soil. The tolerability of soils with low gypsum content gave good results compared to the high soil content of gypsum because gypsum dissolves in water in the case of high gypsum-soils
Keywords: Bearing capacity; Ring footing